Toward Effective Disaster Management and Urban Planning: A GIS-Based Spatial Analysis of Historical Disaster Data in Malang Municipality - M. Kahfi Maulana Anggara; Rian Agusdian; Gilang Aulia Herlambang; Fajar Setiawan Yuliano (PANGRIPTA, 2025)
The provision of data and information today is essential not only for generating statistical figures but also for supporting decision- making based on in-depth analysis. In the context of disaster management, spatial data plays a crucial role in identifying the distribution, characteristics, and patterns of affected areas. This research aims to analyze the historical records of disaster events in Malang Municipality spatially using a Geographic Information System (GIS). The data used consists of disaster incidents from 2020 to 2024, which were processed into spatial format and analyzed through spatial join functions to generate distribution maps and frequency summaries by administrative region. The results show that Klojen District recorded the highest number of disaster events with 360 incidents (169 floods, 123 extreme weather events, and 68 landslides). The distribution patterns indicate that floods are scattered randomly, landslides are concentrated along rivers and slopes, while extreme weather events show both linear patterns along roads with dense vegetation and random patterns in residential areas due to the dynamic nature of wind. These findings highlight the importance of preparedness and spatially-based mitigation strategies that consider the characteristics of the affected areas and historical disaster data.